Development of tissue-equivalent phantoms for biomedical ultrasonic applications. (4th February 2008) - Singh, Manju; Singh, H.R.; Kumar, Ashvani; Singh, V.R.; Pant, K.; Sethi, Poonam
Tissue phantoms are, generally, used in the calibration of therapeutic and diagnostic systems. Thus, Tissue-Mimicking (TM) phantoms are developed and studied here for various ultrasonic output parameters. These phantoms have been developed by using agar-based Tissue-Mimicking Materials (TMM) with alumina as an absorption material. A pulser ? receiver (make Panametrics, Model ? 5800, Waltham, MA 02154, USA) has been used to measure ultrasonic velocity and attenuation coefficient, which were found to be 1540?1550 m/s and attenuation 10.0?35.0 dB/m-MHz at frequencies from 2.5 MHz to 5.0 MHz. These ultrasound test phantoms incorporating TM material are useful in the performance evaluation of medical ultrasound systems.